PENERAPAN PENGENDALIAN INTERN TERHADAP PIUTANG USAHA PADA PT. MEGA AUTO CENTRAL FINANCE CABANG BANGKINANG - Suci Aprilia; Efi Susanti (STIE Bangkinang Publishing, 2020)
This study aims to study the application of controls over accounts receivable at PT. Mega Auto Central Finance (MACF), Bangkinang Branch. research results, publications on the internal control system of trade receivables at PT. Mega Auto Cental Finance has been effective. The research method used is descriptive research using qualitative. This research was conducted by comparing the internal controls implemented by the company by transferring COSO which consists of 5 components, namely control, control activities, risk assessment, information and communication, and monitoring.